Decreasing of heterogeneity in black tiger prawn (Penaeus monodon) and white shrimp (Litopenaeus vannamei) broodstocks and their fry produced in hatchery - Bambang Widyo Prastowo; Rahayu Rahardianti; Evi Maftuti Nur (Jurnal Akuakultur Indonesia)
Domestication and genetic improvement of shrimp are required towards production of superior broodstock.  BBPBAP Jepara had performed study on evaluation of genetic diversity of black tiger and white shrimp broodstock and their progenies produced in hatchery, using Restriction Fragment Length Polymorphism (RFLP)-mtDNA method.  Amplification of black tiger shrimp mtDNA used primers designed based on 16S rDNA sequences, and the products were restricted by Nde II enzyme.  While the primers for white shrimp was based on COIL and COIH sequences, and their PCR products were digested with Nla III.  The results of study showed that heterogeneity of tiger shrimp derived from Aceh waters was 0.1063, while their F1 progeny was 0.0494.  Heterogeneity of male tiger shrimp from Aceh waters and their progeny was 0.2811 and 0.1023, respectively, while of female was 0.1594 and 0.0940, respectively.  Heterogeneity of F1 tiger shrimp from Sunda Strait was 0.0405, while their F2 was homozygous.  Heterogeneity of F1 male and female tiger shrimp from Sunda Strait was 0.0641 and 0.1567, respectively, while of F2 was homozygous for both male and female.  Heterogeneity value of F1 white shrimp from Hawaii was 0.0069, while the F2 was homozygous.  Heterogeneity of F1 male and female white shrimp was 0.0099 and 0.0234, respectively, while of their F2 for both male and female were homozygous.  Homozygous has been found in F1 of white shrimp broodstock from Florida.  Based on the results of study, genetic variation of tiger shrimp and white shrimp broodstock used in hatchery were decrease.  Combination of conventional selective breeding approach and molecular technique may be useful to faster to meet the goal of domestication and quality improvement of penaeid species in Indonesia.